French pharmaceutical industry and biologically active natural products from Pierre Fabre Laboratories - B, David; R, Belle; C, Dunouau; P, Fleury; P, Fleury; -Pouny, Granger; P, Negol; M-J, Serrano (Malaysian Journal of Science, 2000)
The industrial preparation and the bioactivity of the anticancer drug, Navelbine, were discussed. The active components of Ruscus aculeatus L., a plant used in the treatment of veinous insufficiency, were also mentioned. Structural elucidation of these compounds was reported.